New Product Development and Performance in the Banking Industry - Fong, Sook-Fun; Lo, May-Chiun; T., Ramayah (Asia-Pacific Institute of Management, 2014)
In this competitive environment, the path to create and develop new products is a series of difficult trials. Considering the potential cascading effect that new product development could have on an organisation’s performance, previous researches may have under-estimated the impact of new product development on organisation performance. The main objective of this article is to hypothesise the impact of new product development on organisation performance. Two hundred and fifty banks’ customers voluntarily participated in this study. SmartPLS 2.0 (M3), also known as partial least squares (PLS), was applied to test the hypotheses that comprised of firm image, brand strength, market sensing capability, product innovativeness and new product quality on new product performance, and subsequently bootstrapping was conducted to investigate the standard error of the estimate and t-values. The findings revealed that four types of new product development factors, namely, firm image, brand strength, product innovativeness and new product quality were found to be positively related to new product performance. Potential limitations of the study and directions for future research are discussed further.